Pemetaan Kliping Digital Perpustakaan Badan Litbang dan Diklat Kemenag RI Tahun 2019-2023 - Khoiriah, Intan Nur; Maryam, Siti (Librarianship in Muslim Societies, 2025)
This article discusses the results of a study entitled Mapping of Digital Clippings of the Library of the Research and Development and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia. The data studied were clippings from 2019-2023. They were analyzed quantitatively using bibliometrics to analyze the trends contained in the clippings, including media trends, author (journalist) trends, and topic or subject trends from the clipped writings. Data were obtained from the Google Drive Spreadsheet linked in the Instagram bio @perpuskemenagri. The study's findings indicate that the digital clippings for the 2019-2023 period studied consisted of 9299 article titles, came from 8 newspapers, and were written by 808 writers/journalists. Republika emerged as the dominant newspaper, and Fuji Eka Permana as the most productive writer with 624 publications, and the topic "Hajj and Umrah" was the most dominant topic, with 1267 titles during the period. The analysis of topic dynamics illustrates a shift in themes, such as the dominance of "halal and haram" in 2019, followed by "Covid-19 pandemic" in 2020 and 2021, and "hajj and umrah" in 2022 and 2023. Other topics such as culture, research, and politics are less frequently discussed in articles. This study outlines the progression of religious issues in Indonesia and has the potential to support further analysis on how digital clippings influence the dissemination of religious information to the public.